2017
DOI: 10.1002/jcp.25736
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor‐α Increases Claudin‐1, 4, and 7 Expression in Tubular Cells: Role in Permeability Changes

Abstract: Tumor necrosis factor-α (TNFα), is a pathogenic cytokine in kidney disease that alters expression of claudins in tubular cells. Previously we showed that in LLC-PK cells TNFα caused a biphasic change in transepithelial resistance (TER) consisting of an early drop and recovery, followed by a late increase. However, the underlying mechanisms and the role of specific claudins in the TER effect remained incompletely understood. Here we sought to define how TNFα affects claudins 1, 4, and 7 in tubular cells and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…MAPK/JNK signalling pathway was reported to be involved in regulating EMT. Phosphorylated JNK may also affect tight junction (TJ) through regulation of claudins . Our qRT‐PCR and WB results further confirmed this phenomenon.…”
Section: Discussionsupporting
confidence: 77%
“…MAPK/JNK signalling pathway was reported to be involved in regulating EMT. Phosphorylated JNK may also affect tight junction (TJ) through regulation of claudins . Our qRT‐PCR and WB results further confirmed this phenomenon.…”
Section: Discussionsupporting
confidence: 77%
“…Cldn1, Cldn3 and Cldn4 were classified to pore‐sealing Cldns in Cldn family. They fucntion as a barier to stop water, ions and molecules from passing through, which would decrease permeability of the epithelium (Khan and Asif, 2015; Amoozadeh et al , 2017). Therefore, the higher expression of Cldn1 and Cldn3 might stop saliva components passing through the acinar epithelium and reduce salivary secretion in diabetes SMGs.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that Cldn1 and Cldn3 were upregulated, while Cldn10 and Ocln were downregulated in db/db mice. Cldn10 was reported to be pore‐forming claudins, which can increase TJ permeability (Khan and Asif, 2015; Amoozadeh et al , 2017). Therefore, lower Cldn10 level might reduce TJ permeability and inhibit salivation through the paracellular pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The following antibodies against tight junction molecules were from Thermo/Invitrogen and have been validated earlier (19,69,90): claudin-2: monoclonal mouse antibody (catalog no. 325600) (used for Western blotting) and polyclonal rabbit antibody (catalog no.…”
Section: Materials and Antibodiesmentioning
confidence: 99%